Chemical investigation of novel ascomycetes using PCR based screening approaches - Jumpathong J. (2014)
Fungi are well known for a wealth of pharmacologically important activities and agrochemical properties. Polyketides that are widely found in fungi, are a large group of secondary metabolites which exhibit diversity in their function and structure. Here we described an investigation of three fungal strains which were prospected for production of polyketides. The aim of this work was to employ the diversity of reducing type I polyketide synthase genes in these fungi using a molecular and bioinformatics approaches as a mini tool. A degenerate primer pair for highly reduced PKSs was newly designed and used together with ketosynthase primers for amplification. One hundred and thirty-eight clones were sequenced. Ten KS domain sequences were isolated, using two primer pairs specific for highly reduced type PKSs. This study revealed four sequences from Emarcea castanopsidicola, four ketosynthase sequences from Gaeumannomyces amomi and two sequences from Leiosphaerella amomi, respectively. Bioinformatic techniques were employed to identify a group of these KS domain sequences. Based on these sequences suggested that rapid screening provided the potential to explore significant PKS structural diversity. Hence chemical investigation had been conducted and exhibited nine compounds. The endophytic fungus L. amomi was cultivated and elucidated linoleic acid, ergosterol and an unidentified sterol in the extracts. Linoleic acid, sitosterol, and p-hydroxybenzoic acid were isolated from the saprobic fungus E. castanopsidicola. We first isolated a new polyketide, stemphol 1-O-β-D-galactopyranoside together with four known metabolites; stemphol, kojic acid, ergosterol, indole-3-carboxylic acid from an ethyl acetate extract of the cultures of G. amomi. Stemphol was classified as a phenolic lipid or resorcinolic lipid, which have biopharmacological, biomedical, and biotechnological importance. However, recent researches have revealed that these molecule types are synthesized by 2′-oxoalkylresorcinolic acid synthase. The prospective KS domain sequences from this study will be used as probes to isolate putative PKS genes. A gene cluster responsible for PK biosynthesis should be confirmed by determination of PK products generated by these enzymes. © 2011 Springer Science+Business Media B.V.